ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2014) - Satyaning Ayu Firdayani (AKT 16 UMY, 2016)
This study aimed to analyze the factors that affect the timeliness of financial statements of public companies in Indonesia. Factors tested in this study is the profitability, the size of the company, the audit committee, the audit opinion as independent variables while timeliness as the dependent variable. The subjects were companies listed in Indonesia Stock Exchange 2013-2014 period. The data used in this research is secondary data and sample selection using purposive sampling method where the total of sample are 130 for 2 years. The analytical tool used is the logistic regression analysis at a significance level of 5%. Hypothesis testing results show that the negative effect on the audit committee timeliness of financial reports. However, no evidence that profitability, firm size and audit opinions affect the timeliness of financial reports. Keywords: Timeliness, financial statements, profitability, size of company, the audit committee, the audit opinion.